2014
DOI: 10.1093/ageing/afu027
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal levels of brain metabolites may mediate cognitive impairment in stroke-free patients with cerebrovascular risk factors

Abstract: abnormal concentrations of brain metabolites and decreased glutamate plus glutamine concentration may play an important role in the pathophysiology of VRF-associated cognitive impairment. Brain metabolites detected by (1)H MRS may serve as important markers for monitoring VRFs burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Abnormality of these signals had been demonstrated in a number of central nervous system diseases [ 19 , 20 ]. Similar to our previous study [ 13 ], we found that aCAS patients had lower NAA/Cr ratio in the left hippocampus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Abnormality of these signals had been demonstrated in a number of central nervous system diseases [ 19 , 20 ]. Similar to our previous study [ 13 ], we found that aCAS patients had lower NAA/Cr ratio in the left hippocampus.…”
Section: Discussionsupporting
confidence: 92%
“…Since previous study had demonstrated that abnormal level of hippocampus metabolites may mediate cognitive performance, we selected 4–6 voxels from both hippocampi using workstation Spectroscopy software [ 13 ]. Then the concentrations of N -acetyl-aspartate (2.02 ppm), choline (3.22 ppm), creatine (3.02 ppm), the ratio of NAA/Cr, and the ratio of Cho/Cr were measured in each selected voxel.…”
Section: Methodsmentioning
confidence: 99%
“…VRFs could function alone or together to affect cognitive performance. Our previous work has shown that, with the aggregation of VRFs, old stroke‐free adults demonstrated worse cognitive performance and more abnormal concentrations of brain metabolites in the hippocampus . This may also apply to the young adults group.…”
Section: Discussionmentioning
confidence: 90%
“…In high levels of VRFs burden, the prefrontal N-acetylaspartate/creatine (NAA/Cr) ratios were markedly lower than the low-risk individuals. This was associated with executive function via a magnetic resonance spectroscopy (MRS) study (Sun et al, 2014 ). The mitochondrial morphological abnormalities that were attributed to oxidative stress were identified in the DLPFC, where mRNA of mitochondrial proteins was expressed intensively, as vital part of the AD progression (Ansari and Scheff, 2010 ).…”
Section: Discussionmentioning
confidence: 99%